2018
DOI: 10.1007/s00268-018-4781-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing and Retaining African Surgeons Working in Rural Hospitals: An Analysis of PAACS Surgeons with Twenty‐Year Program Follow‐Up

Abstract: Our study shows that PAACS general surgery training program has a high retention rate of African surgeons in rural settings compared to all programs reported to date, highlighting a multifaceted, rural-focused approach that could be emulated by surgical training programs worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…This is supported by research conducted in high-income countries across different rural contexts and health professions where matters relating to people and place (including supportive work environments) are often identified as being of high importance in attracting and retaining health professionals [30,32,[38][39][40]. Further exploration is needed as to whether these community/place recommendations could have relevance for rural-based health professionals from low-income countries given the differences in cultures and health and education systems [41,42]. On the other hand, the recommendations made relating to organisational/workplace and role/career domains are likely highly contextual and relate specifically to Australia's AHPs working in public sector services.…”
Section: Broader Relevance Of the Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by research conducted in high-income countries across different rural contexts and health professions where matters relating to people and place (including supportive work environments) are often identified as being of high importance in attracting and retaining health professionals [30,32,[38][39][40]. Further exploration is needed as to whether these community/place recommendations could have relevance for rural-based health professionals from low-income countries given the differences in cultures and health and education systems [41,42]. On the other hand, the recommendations made relating to organisational/workplace and role/career domains are likely highly contextual and relate specifically to Australia's AHPs working in public sector services.…”
Section: Broader Relevance Of the Recommendationsmentioning
confidence: 99%
“…For this group, income and work conditions are major factors for attraction and retention [38,39]. In addition, recruitment of rural doctors may be influenced by financial enticements such as bonded placements, loan repayment schemes or other financial incentives, and these types of financial benefits are less commonly on offer to AHPs and nurses [41,42].…”
Section: Broader Relevance Of the Recommendationsmentioning
confidence: 99%
“…A study from Malawi found no general surgeons, anesthetists, or biomedical technicians in 23 rural district hospitals with a catchment of about five million people as opposed to 27 general surgeons, nine anesthetists, and five biomedical technicians in urban central hospitals with a catchment of two million people [ 31 ]. This disparity is even more acute in rural West Africa than the ECSA region as decentralization of training of surgeons (using rural and district hospitals as opposed to urban teaching hospitals alone) has encouraged trainees to stay in ECSA rural areas [ 105 , 109 ]. The West African College of Surgeons relatively recently introduced a 6-month rural posting earlier in specialist surgical training [ 110 , 111 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…Medical schools are frequently located in the capital or other major cities, and medical students are more likely to come from urban areas as well. Multiple studies across several SSA countries reveal homogeneity in concerns about pursuing rural service: poor health facility equipment and infrastructure, lack of supervision and management support, limited career advancement opportunities, spartan living conditions, cultural and language differences, and distance from family [12]. However, there are also predictors and motivators for rural practice.…”
Section: Discussionmentioning
confidence: 99%